PENGARUH SUDUT KELENGKUNGAN INTAKE MANIFOLD TERHADAP PERFORMA MESIN SEPEDA MOTOR: THE EFFECT OF INTAKE MANIFOLD ANGLE OF CURVEMENT ON MOTORCYCLE ENGINE PERFORMANCE - Vicky Styo Pramono (Program Studi Teknik Mesin PSDKU Polinema Kediri, 2022)
In a gasoline engine, the intake manifold is an important component because the intake manifold functions as an inlet for air and fuel into the combustion chamber. The shape of the curvature of the intake manifold affects the air entering the combustion chamber. Because to produce a homogeneous mixing of air and fuel to produce perfect combustion. Of course it has an impact on the torque and power produced.Torque and power testing using a special dynotest tool. The research conducted has several variables that will affect the output of this study, namely the independent variables include variations in the angle of curvature of the manifold using standards, 140˚, 155˚, and 160˚, type of fuel with ron 90 and engine speed (RPM). The dependent variable is torque, power and fuel consumption which will be tested. The hypothesis in this study is the alternative hypothesis (H1) because according to the analysis changes in the curvature of the manifold can affect the performance of the motorcycle engine. Impact results have the greatest influence on the power produced, with an angle of 100 ̊ indicating superior power than other intake manifolds. For Dmax (Maximum Power) right at 6500 rpm engine speed with an average of 5.86Hp. Meanwhile, the intake manifold with a curvature angle of 120 shows the best results with Tmax (Maximum Torque) at 5000 rpm engine speed with an average of 7.16nm.